Implementation of CAPM and Performance Analysis of Stock Portfolio with Risk-Adjusted Return on LQ45 Stock - Joseph Tendean; Tarsicius Sunaryo (Budapest International Research and Critics University, 2022)
This study aims to analyze the return and risk of the LQ45 stock group on the Indonesia Stock Exchange and determine investment decisions using the Capital Asset Pricing Model by distinguishing between undervalued and overvalued stocks based on 2017 data. – 2021, so that a portfolio that can produce optimal returns can be formed. Based on Treynor's performance measures, 24 stocks were found to be superior to the market. By using Jensen's Alpha it was found that 24 stocks had a positive alpha (outperform) compared to other stocks studied. The results also show that 14 stocks have a beta coefficient of less than one (<1) and 30 stocks have a beta coefficient of more than one (>1); 24 undervalued stocks and 20 overvalued stocks. In this study, it was also found that stocks with high betas do not automatically provide high returns.